Hurricanes, Climate Change Policies and Electoral Accountability - Stefano Gagliarducci; M. Daniele Paserman; Eleonora Patacchini (Institute of Labor Economics (IZA), 2019)
This paper studies how politicians and voters respond to new information on the threats of climate change. Using data on the universe of federal disaster declarations between 1989 and 2014, we document that congress members from districts hit by a hurricane are more likely to support bills promoting more environmental regulation and control in the year after the disaster. The response to hurricanes does not seem to be driven by logrolling behavior or lobbysts' pressure. The change in legislative agenda is persistent over time, and it is associated with an electoral penalty in the following elections. The response is mainly promoted by representatives in safe districts, those with more experience, and those with strong pro-environment records. Our evidence thus reveals that natural disasters may trigger a permanent change in politicians' beliefs, but only those with a sufficient electoral strength or with strong ideologies are willing to engage in promoting policies with short-run costs and long-run benefits.
Keywords: D70; D72; H50; Q54; 330; U.S. Congress; hurricanes; legislative activity